Immune profiling and functional analysis of NK and T cells in ataxia telangiectasia - Graafen, Lea; Heinze, Annekathrin; Albinger, Nawid; Salzmann-Manrique, Emilia; Ganß, Franziska; Hünecke, Sabine; Cappel, Claudia; Wölke, Sandra; Donath, Helena; Trischler, Jordis; Theilen, Till-Martin; Heller, Christine; et al. (Frontiers in Immunology, 2024)
Ataxia telangiectasia (AT) is a rare autosomal-recessive disorder characterized by profound neurodegeneration, combined immunodeficiency, and an increased risk for malignant diseases. Treatment options for AT are limited, and the long-term survival prognosis for patients remains grim, primarily due to the emergence of chronic respiratory pathologies, malignancies, and neurological complications. Understanding the dysregulation of the immune system in AT is fundamental for the development of novel treatment strategies. In this context, we performed a retrospective longitudinal immunemonitoring of lymphocyte subset distribution in a cohort of AT patients (n = 65). Furthermore, we performed FACS analyses of peripheral blood mononuclear cells from a subgroup of 12 AT patients to examine NK and T cells for the expression of activating and functional markers. We observed reduced levels of peripheral blood CD3+CD8+ cytotoxic T cells, CD3+CD4+ T helper cells, and CD19+ B cells, whereas the amount of CD3−-CD56+ NK cells and CD3+CD56+ NKT-like cells was similar compared with age-matched controls. Notably, there was no association between the age-dependent kinetic of T-, B-, or NK-cell counts and the occurrence of malignancy in AT patients. Additionally, our results indicate an altered NK- and T-cell response to cytokine stimulation in AT with increased levels of TRAIL, FasL, and CD16 expression in NK cells, as well as an elevated activation level of T cells in AT with notably higher expression levels of IFN-γ, CD107a, TRAIL, and FasL. Together, these findings imply function alterations in AT lymphocytes, specifically in T and NK cells, shedding light on potential pathways for innovative therapies.